2011 IEEE 61st Electronic Components and Technology Conference (ECTC) 2011
DOI: 10.1109/ectc.2011.5898531
|View full text |Cite
|
Sign up to set email alerts
|

Outperformance of Cu pillar flip chip bumps in electromigration testing

Abstract: Standard NiAu/SAC (SnAgCu) solder bumps are compared with Cu pillar bumps in terms of their electromigration behavior. Both bump configurations are flip chipped onto package substrates with a thick Cu finish. The Cu pillar bumps, which are soldered with a thin SnAg cap, outperform the standard solder flip chip bumps due to the fast formation of an intermetallic phase which covers the full solder stand-off height. These bumps do not show any significant electromigration damage and do not fail within reasonable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Figure 29 shows SEM images of solder bumps under thermal stress without and with EM stress for both standard solder bump and Cu pillar bump. 72 Standard bumps with Ni/Au UBM show a consistent failure mechanism of micro-structural degradation through void formation at the interface of solder and IMC, and this occurs for all test conditions used C and 300-500 mA). However, Cu pillar bumps did not show any electrical, nor micro-structural degradation.…”
Section: Reliability Assessment Of Cu Pillar Bumpsmentioning
confidence: 79%
See 1 more Smart Citation
“…Figure 29 shows SEM images of solder bumps under thermal stress without and with EM stress for both standard solder bump and Cu pillar bump. 72 Standard bumps with Ni/Au UBM show a consistent failure mechanism of micro-structural degradation through void formation at the interface of solder and IMC, and this occurs for all test conditions used C and 300-500 mA). However, Cu pillar bumps did not show any electrical, nor micro-structural degradation.…”
Section: Reliability Assessment Of Cu Pillar Bumpsmentioning
confidence: 79%
“…72 A clear difference in EM behavior was observed between standard NiAu/SAC and Cu pillar bumps. Figure 29 shows SEM images of solder bumps under thermal stress without and with EM stress for both standard solder bump and Cu pillar bump.…”
Section: Reliability Assessment Of Cu Pillar Bumpsmentioning
confidence: 97%
“…The solder alloy in those very tiny solder bumps makes EM testing mandatory, as high current densities and high temperatures are expected. Work performed by other authors shows that EM performance can be improved by transforming Sn into tin-copper intermetallics (IMCs) [9]. If, as in our experiments, parts with large CTE mismatch are used, thermal cycling performance would decrease dramatically due to the low ductility of the intermetallic compounds [10].…”
Section: Discussionmentioning
confidence: 88%
“…[9][10][11][12][13][14] Another approach that has been reported for packages with pillar microbumps shows that a smaller bump resistance increase with current when the standard solder bumps and Cu pillar microbumps are compared in terms of their electromigration performance. 25) That is, the electromigration behavior of a Cu pillar microbump under current-stressing conditions was more stable than that of a conventional solder bump because the failure occurred in the Al trace rather than in the Cu pillar microbump.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, Cu pillar microbumps are compared with standard solder bumps in terms of their electromigration and mechanical behavior. Labie et al 25) have been reported that compared with the pillar bumps, solder bumps show a larger temperature increase with current, which is particularly obvious as soon as the melting point of the solder is reached. Zhan et al 26) have studied the mechanical reliability of micro joints with different bonding conditions by using the die shear test.…”
Section: Introductionmentioning
confidence: 99%